2020
DOI: 10.1017/s0022029920000060
|View full text |Cite
|
Sign up to set email alerts
|

Rumen function in goats, an example of adaptive capacity

Abstract: The aim of this Research Reflection is to describe the basic rumen function of goats and its modification in response to environmental factors, as well as to discuss similarities and differences when compared to other ruminants. In so doing we shall reveal the adaptive capacity of goats to harsh environments. The basic rumen function in goats is similar to other species of ruminants, as stressed by the opportunity to apply the updates of feeding systems for ruminants to goats. The rumen epithelium acts as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…At the EU scale, the CAP has been recognized as a key tool to achieve a sustainable transformation and best management practices. Concerning the adaptation measures of SR farms in the climate change context, a good solution could be to focus on some breeds of goats that are quite tolerant to environmental stressors (Giger‐Reverdin, Domange, et al., 2020; Giger‐Reverdin, Duvaux‐Ponter, et al., 2020). However, the route to sustainable rangeland and SR stock management (Bock et al., 2020; Department for Environment, Food & Rural Affairs, 2021; Natural Resources Conservation Service, 2016) should be embraced by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…At the EU scale, the CAP has been recognized as a key tool to achieve a sustainable transformation and best management practices. Concerning the adaptation measures of SR farms in the climate change context, a good solution could be to focus on some breeds of goats that are quite tolerant to environmental stressors (Giger‐Reverdin, Domange, et al., 2020; Giger‐Reverdin, Duvaux‐Ponter, et al., 2020). However, the route to sustainable rangeland and SR stock management (Bock et al., 2020; Department for Environment, Food & Rural Affairs, 2021; Natural Resources Conservation Service, 2016) should be embraced by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that for ruminants fed the same diet, some develop acidosis while others keep their neutral as observed in cows 37 or goats 38 . It seems that feeding behaviour 39 and rumen adaptive capacity 40 are among the main factors regulating animals’ response to a change of diet. This link needs to be studied in greater depth, and in particular the link between feeding behaviour and evolution of microbiota, and the link between feeding behaviour and feed efficiency 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In cattle and sheep, dietary tannins can create complexes with lignocellulose, inhibiting cellulolytic microorganisms and fibrolytic enzymatic activity, and increasing rumen physical filling, with negative consequences on voluntary DMI and fiber digestion (62,63). However, goats and other browsing animal species are able to produce tannin-binding saliva and stimulate the proliferation of tannin-tolerant bacteria, mostly overcoming the negative effects of tannins on intake and nutrient digestion (64,65). da Silva et al (66) recently demonstrated that a dietary concentration of CT equal to 5% DM did not affect the DMI and nutrient intake of goats from different genotypes.…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentsmentioning
confidence: 99%